Formação ambiental na escola do campo: uma análise documental sob o olhar do ecoletramento - Silva, Claudionor Renato da (Universidade Federal de São Carlos, 2011)
Ecological sustainable environmental formation is in the basis of public education policy on country Education so that socioenvironmental questions become part of the curriculum, therefore, of the syllabus. In this theoretical documental investigation we inquire about the ways this proposal of environmental formation occurs in a country school in São Paulo state. We have adopted the perspective of ecoliteracy to understand this formation. The following documents were object of study: the School Pedagogical Project, the Teacher s Plan and the Class Diary of the 5thgrade of an elementary school. After the pre-analysis, a preliminary analysis was carried out indicating: (1) the context of production of the document; (2) the author/authors; (3) authenticity reliability of documents; (4) the nature of the text; (5) key concepts and internal logic of the text. The next step was an interpretive analysis with the objective to identify and to configure how environmental formation is processed in a country school. The results indicated the presence of the environmental formation discourse that reveals itself by means of key elements (words and sentences) that dialogue with the bases of ecoliteracy. These elements pervade the discourse of the Pedagogical Project but in the Teacher s Plan and in the Class Diary that are perspectives to guide the pedagogic actions directly we observed a more specific presence of Science and Geography. We can infer that as the Pedagogical Project has a more comprehensive and ideological discourse according to the directions of environmental formation, such as recommended in public policy on country education, the environmental discourse elements are more explicit and orderly . In the other two documents, even if one of them focuses technical and organic aspects of curriculum (Teacher Plan) and the other is the mirror of daily classroom routine (Class Diary) the discourse of environmental formation becomes less dense and more fragmented. The research question is answered at the same time that it places the ecoliteracy not only as a perspective for environmental formation in country Education but as a possible, theoretical and methodological construct for the curriculum.
Environmental formation in a country school: a documental analisys from the perspective of ecoliteracy
Keywords: Educação ambiental; Escola do campo; Ecoletramen; Environmental formation; Country school; Ecoliteracy; CIENCIAS HUMANAS::EDUCACAO